From Espinee to Sambocade: Flowers in the Recipes of Medieval England - Hieatt, Constance B; Hosington, Brenda M (Petits Propos Culinaires, 1998)
The article looks at one of the differences between medieval French and English recipes in the early middle ages finding that in the latter cuisine, flowers as appear as ingredients rather than mere decoration.